2022
DOI: 10.3390/en15010337
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Internal Combustion Engine Ignition Systems with a Circuit Containing Fractional-Order Elements

Abstract: This paper discusses the research and analysis of the dynamics of high-voltage generating systems. The test subject is an ignition system modelled by a set of two induction coils with an open ferromagnetic core that constitutes an ignition coil. The essence of the tests involved the application of magnetic coupling of the fractional order that enabled taking into account the non-idealities of the coils and the connector that implements the ignition point. The paper contains the results of a theoretical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…To reveal the influence each component parameter has on the ignition system current-voltage performance, electrical models of the components of inductive ignition systems have been presented in the works of Stevenson et al, 5 Wang et al, 6 Ro´_ zowicz et al 7,12,13 , Korenciak et al, 14 and Qisong et al 15 However, despite the fact that the models shown in Refs. [5][6][7][12][13][14][15] take into account the resistances and capacitances of the hightension wire and the spark plug, parasitic capacitance of the switch, and mutual inductance, all of them deal with a solid-state switch that is, a BJT, a MOSFET, or an IGBT, modeled as ideal switches (even in the case when some Zener-based clamp is added to limit the voltage output). Stevenson et al 5 state that some inaccuracy of their modeling results is due to the switching element model.…”
Section: An Overview Of Modeling Methodologies For Inductive Ignition...mentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal the influence each component parameter has on the ignition system current-voltage performance, electrical models of the components of inductive ignition systems have been presented in the works of Stevenson et al, 5 Wang et al, 6 Ro´_ zowicz et al 7,12,13 , Korenciak et al, 14 and Qisong et al 15 However, despite the fact that the models shown in Refs. [5][6][7][12][13][14][15] take into account the resistances and capacitances of the hightension wire and the spark plug, parasitic capacitance of the switch, and mutual inductance, all of them deal with a solid-state switch that is, a BJT, a MOSFET, or an IGBT, modeled as ideal switches (even in the case when some Zener-based clamp is added to limit the voltage output). Stevenson et al 5 state that some inaccuracy of their modeling results is due to the switching element model.…”
Section: An Overview Of Modeling Methodologies For Inductive Ignition...mentioning
confidence: 99%
“…The models shown in Refs. 6,7,[12][13][14][15][16] consider the resistances and capacitances of the high-tension wire and the spark plug, parasitic capacitance of the electronic switch, and mutual inductance.…”
Section: The Coil Modelingmentioning
confidence: 99%
“…Kemudian aki menyuplai arus dan tegangan pada ignition coil untuk menghasilkan output tegangan delco. Tegangan output delco didistribusikan pada empat spark plug yang mengakibatkan penyalaan intensitas bunga api secara bergantian [31]. Hasil output tegangan delco dihubungkan pada mikrokontroler Arduino untuk memantau tegangan, suhu, putaran motor fan pada LCD [32].…”
Section: Metode Penelitianunclassified
“…In this section, the optimized 2.06-order filter and the 2nd-order filter are analyzed in the frequency domain and compared with the 2nd-order Bessel filter, which is a commonly used integer-order linear phase filter, and the transfer function of the 2nd-order Bessel filter with normalized cutoff frequency is shown in (18).…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…The circuit realization of 2.06-order filter requires 1.06-order capacitor. Although much academic research has been done on fractional-order capacitors [18]- [20], no commercially available fractional-order capacitors are currently in production, so this paper uses the Foster I RC network and general impedance converter (GIC) to approximate the 1.06 order capacitors as shown in Figure 6. The element values of the Foster I RC network computed using the approach described in [21] and the continued fraction expansion method [22] are shown in Figure 6.…”
Section: Circuit Simulationmentioning
confidence: 99%